Intramuscular neridronate for the treatment of complex regional pain syndrome type 1: a randomized, double-blind, placebo-controlled study. (June 2021) - Varenna, Massimo; Braga, Vania; Gatti, Davide; Iolascon, Giovanni; Frediani, Bruno; Zucchi, Francesca; Crotti, Chiara; Nannipieri, Fabrizio; Rossini, Maurizio
Background: Complex regional pain syndrome type-1 (CRPS-1) is a severely disabling painful disease challenging to treat. This multicenter, randomized, double-blind placebo-controlled trial examined the efficacy of intramuscular (i.m.) neridronate in CRPS-1 patients. Methods: A total of 78 patients diagnosed with CRPS-1 (aged 59.5 ± 10.3, 66.7% female) were randomly assigned to 25 mg (i.m.) neridronate ( N = 41) given once daily for 16 consecutive days or placebo control ( N = 37). Efficacy was assessed after 30 days using a visual analogue scale (VAS) pain score and the number of patients achieving ⩾50% reduction in VAS score. Change in clinical signs and symptoms, quality of life (QoL) using Short Form Health Survey (SF-36) and the McGill Pain Questionnaire were also assessed. Results: After 30 days, VAS score decreased significantly to a greater extent in neridronate-treated patients versus placebo (31.9 ± 23.3 mm versus 52.3 ± 27.8 mm, p = 0.0003). Furthermore, the proportion of patients achieving a VAS reduction of ⩾50% was greater in the neridronate group (65.9% versus 29.7%, p = 0.0017). Clinical signs and symptoms were improved significantly in the neridronate group versus placebo for edema (72.5% versus 79.9%, p = 0.03), pain during motion (70% versus 83.3%, p = 0.0009), allodynia (20% versus 63.3%, p = 0.0004), and hyperalgesia (20% versus 56.7%, p = 0.0023). Whereas no difference was observed for QoL measures using the SF-36 questionnaire, three of the four pain variables using the McGill Pain Questionnaire improved significantly in the neridronate group. No serious drug-related adverse events were reported during the study. Conclusion: In patients with acute CRPS-1, i.m. injections of 25 mg neridronate were associated with clinically relevant benefit compared with placebo controls. Trial registration: EU Clinical Trials Register:https://www.clinicaltrialsregister.eu/ctr-search/search?query=2014-001156-28